The Tourist Region - Liszewski , Stanisław (Turyzm/Tourism, 2003)
Having discussed the academic achievements regarding the notion and delimitation of the tourist region, the author suggests his own original definition. He has based this definition on the concentration of tourist, and then isolated seven types of functional tourist region.